2016
DOI: 10.15201/hungeobull.65.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Modelled spatio-temporal variability of air temperature in an urban climate and its validation: a case study of Brno, Czech Republic

Abstract: This study compares the results of air temperature model simulations with real temperature measurements in an urban environment. The non-hydrostatic micro-scale model MUKLIMO_3 is used to predict air temperature fi elds in Brno (Czech Republic). The development of the air temperature fi elds on three diff erent days was modelled which characterising the radiation-driven weather conditions with high temperature that occurred during the summer of 2015. This analysis demonstrates that the model is able to reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
2
17
0
1
Order By: Relevance
“…This overestimation was clear in comparisons of model and measurements temperatures (Figure 7). This model attribute was reported previously by Geletič et al (2016). The only station with good nocturnal fitting was B4.…”
Section: Conclusion and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This overestimation was clear in comparisons of model and measurements temperatures (Figure 7). This model attribute was reported previously by Geletič et al (2016). The only station with good nocturnal fitting was B4.…”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…It also uses categorisations of proportions of surfaces of varied kinds using an established scale: built-up, impermeable, and permeable surface parts such as vegetation cover and soil (Sievers et al, 1983). The model has been used for UHI studies in various cities, for example, Vienna (Žuvela et al, 2014), Brno (Geletič et al, 2016(Geletič et al, , 2018, Bratislava (Holec and Šťastný, 2017), Szeged (Gál and Skarbit, 2017) or comparison of five central European cities (Bokwa et al, 2015;Bokwa et al, in print). Several model inputs are necessary, including layers of a digital elevation model, a LC/LU map, parameters of LC/LU classes, and meteorological inputs.…”
Section: Model Muklimomentioning
confidence: 99%
“…For instance, Alexander et al [15] revealed distinctive heat fluxes for some LCZs and concluded that LCZ classification provides a useful sampling framework for the derivation of the land-cover fractions needed to run surface-energy balance models. Zuvela-Aloise et al [16] and Geletič et al [17] used LCZs as input to MUKLIMO_3, a non-hydrostatic micro-scale air temperature model. Further, Skarbit et al [18,19] worked on the relations between LCZ and LST.…”
Section: Introductionmentioning
confidence: 99%
“…However, such measurements, even supplemented by measurements from a dense network of automatic stations, often prove insufficient to describe and understand fully the spatial variability of air temperature in urban areas [17,20]. These measurements are insufficient especially in terms of their ability to characterize temperature spatial distribution in detail, as the result may be dependent on the number of "point" measurements, the method of interpolation and more.…”
Section: Introductionmentioning
confidence: 99%
“…While we have found that it is very low in Žilina, the city is also less prone to experiencing heatwaves compared to the other two study areas-thanks to its basin location and higher elevation, the average high temperatures in summer are around 2 • C lower. Presented results of UGS assessment will serve as the input data for the definition of the local climate zones [39], and the MUKLIMO model [40,41] will be tested in the study areas. Further research oriented on the relationship between the spatial pattern of urban features and land surface temperature in the study areas will bring deeper insight into the effects of UGS on local urban microclimate.…”
Section: Assessment Of Urban Ecosystem Servicesmentioning
confidence: 99%